Detection of Salmonella and several common Salmonella serotypes in food by loop-mediated isothermal amplification method - Zhongqiang Chen; Ke Zhang; Huan Yin; Qi Li; Lan Wang; Zhiguo Liu (Food Science and Human Wellness)
Salmonella Choleraesuis, S. Enteritidis and S. Typhimurium are the main pathogens that contaminate animal products and cause human Salmonella food poisoning. To establish the loop-mediated isothermal amplification (LAMP) method for the rapid detection of Salmonella and 3 common Salmonella serotypes, inner and outer primer sets targeting Salmonella invE gene and 3 serotype-specific genes fliC, lygD and STM4495 were designed. The LAMP reaction conditions were optimized. The specificity of LAMP primers was identified by testing 10 different bacterial strains including S. Choleraesuis, S. Enteritidis and S. Typhimurium. Take S. Choleraesuis as example, the detection limit of LAMP assay was 1.33 × 101 CFU/mL for bacteria culture and 2.0 × 101 CFU/mL for simulated pork sample. The results show that LAMP is a rapid, sensitive and specific method for Salmonella detection and can be used for the rapid detection of Salmonella in food.